A Complex Puzzle : Realities of English-speaking Seniors in Quebec - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Ideally, we would grow old in good health, maintaining physical and mental well-being and enjoy social inclusion and economic security in a respectful and supportive environment. However, despite strategies to build toward such an ideal in the face of an aging population, public policy and programs at all levels of government largely continue to be shaped by the needs of younger generations. This brief looks at challenges that Quebec’s English-speaking seniors face. It draws on research and policy efforts aimed at understanding and improving the aging experience in the province.

Public Services in English Quebec : A Primer - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Who can access public services in English in Quebec, and under what circumstances? The answer depends on which level of government - federal or provincial - is involved, since each has its own language rules. While Quebec operates with French as its only offi cial language, Canada recognizes both English and French at the federal level. This brief explores how Quebec’s French-first policy coexists with federal bilingualism, how this affects English use, and by extension English speakers, in the areas of education, healthcare, and public administration.

Linguistic Identity Complexities in English-speaking Quebec - Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
The prevailing frameworks for categorizing Quebec’s linguistic communities - namely, the Anglophone/Francophone binary and the Anglophone/Francophone/Allophone distinctions - oversimplify the realities many individuals experience. This brief explores some of the complex linguistic identities of English-speaking Quebecers highlighted in the research.

Challenges and Priorities for Quebec’s English-Language Education Continuum - Shoumarova, Lina (Quebec English-speaking Communities Research Network (QUESCREN), 2024)
This brief aims to inform the Standing Committee on Official Languages about challenges experienced in Quebec’s English-language minority education sector, and their impact on the education continuum from early childhood to post-secondary education and beyond. It summarizes findings from 11 research briefs on English-language education that QUESCREN produced and commissioned between 2021 and 2024. Additionally, it outlines priority areas for development in addressing these challenges.

Proposal for Including English-speaking Quebecers in the Programme d'accès a l'égalité en emploi (PAÉE) - Bourhis, Richard Y. (QUESCREN Lunch & Learn Series, 2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

Innovative Mentorship Program Equips English-Speaking Quebecers With Workplace French Skills - Provincial Employment Roundtable (PERT) (2024)

PERT’s Recommendations Included in New Report on the Economic Development of Offi cial Language Minority Communities - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

User Journeys of Language Learners Navigating Québec's French Language Training System - Provincial Employment Roundtable (PERT) (2024)
In recent years, the Québec government has significantly invested in French language training programs to promote greater usage of French in workplaces, schools, and society. Alongside these efforts, public discourse has emerged about the perceptions French-speaking Quebecers hold of English speakers, many of whom believe that English speakers are not committed to learning or using French despite the availability of publicly funded French language training resources. To explore these issues, this study examines the experiences, motivations, and barriers faced by English-speaking individuals in the labour force regarding French language training, particularly following the introduction of new services by Francisation Québec in June 2023. In doing so, we develop a broad typology of different language learners and explore their language-learning journey through interviews regarding their experiences and perceptions of the French language, language training, and navigating Québec’s labour market. We also interview subject matter experts to identify types of language learners and key themes. We then discuss the impact that these different experiences have on language learners’ outcomes, as well as the types of policy and program approaches that could improve their experiences with adult French language training programs.

New Report Calls for Coordinated Action to Tackle Employment Barriers Facing English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

English Speakers in Gaspésie–Îles-de-la-Madeleine Experience the Highest Unemployment Rate in Québec, New Report Finds - Provincial Employment Roundtable (PERT) (2024)

English-speaking Quebec Plays Vital Role in Boosting French, Language Commissioner Says - Quebec Community Groups Network (QCGN) (2024)

English Speakers in the Laurentides Face Growing Economic Challenges, New Report Shows - Provincial Employment Roundtable (PERT) (2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

New Language Directives in Health a Welcome, Significant Step, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

English Speakers in Montérégie Facing Increased Unemployment and Ongoing Economic Disparities as Compared to Francophones - Provincial Employment Roundtable (PERT) (2024)

QCGN Pleased by Motion To Nix Identity Certificate for Health Care - Quebec Community Groups Network (QCGN) (2024)

Suicide Risk for Quebec’s English-speaking Population - Community Health and Social Services Network (CHSSN) (2024)

Health Directives Should Be Scrapped, Not Tweaked, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Income Disparities Between Quebec's English Speakers and Francophones Over Time - Donovan, Patrick; Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief looks at income disparities between English speakers and Francophones in Quebec. It examines changes from the early 20th century, when Anglophones dominated many major industries, through political and cultural shifts between 1940 and 1980 to today’s landscape.

OQLF Has No Business in Quebec Operating Rooms, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

New Census Data for Côte-Nord Shows No Improvement in the Economic Vitality of English Speakers Since 2016 - Provincial Employment Roundtable (PERT) (2024)

Building Bridges Between Communities Valuable, QCGN Annual Meeting Is Told - Quebec Community Groups Network (QCGN) (2024)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Challenges in Early Learning and Child Care for Quebec's English-speaking Community - Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Early childhood education and care (ECEC). Early learning and child care. Nursery school. Preschool. Daycare. Centres de la petite enfance (CPE). There are many names and acronyms, but they all refer to the care and, ideally, educative care of young children in the years before compulsory elementary schooling. Modern wisdom views such programs as essential, and yet, in Quebec, English-speaking families face unique challenges in accessing them. This research brief explores these barriers, current efforts being made to address them, and potential solutions.

Demographic Decline of English Speakers in Certain Regions of Quebec - Bell, Shannon; Donovan, Patrick (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
How is English faring in Quebec? While 2021 census data reflect a recent increase in English usage in the Montreal and Gatineau areas, a more complex portrait emerges when examining other parts of Quebec and longer time periods. The 20th century was marked by a decline in the proportion of English speakers in most Quebec regions. The trend has shifted in the past 20 years, yet a notable decline continues in parts of coastal Quebec, the Eastern Townships, and Rouyn-Noranda. This brief looks at regions experiencing a decline in their English-speaking populations, and considers the forces driving recent changes.

Building Bridges : Perceptions and Realities About the English-speaking Communities of Quebec and their Relationship with French in Quebec and Bilingualism in Canada - Canada. Office of the Commissioner of Official Languages (2024)
The Office of the Commissioner of Official Languages (the Office of the Commissioner) has observed that, in recent years, the English-speaking communities of Quebec (ESCQ) have been the focus of much public discourse and debate in the province. Survey and census data indicate that, overall, the ESCQ are highly bilingual and value Canada’s broader linguistic duality, including the French language. The extent to which the general population is aware of these facets of the ESCQ is not clear, however, and the Office of the Commissioner wished to test the hypothesis that problematic myths may persist. In light of this context and with the modernization of the Official Languages Act by the federal government in 2023, which recognizes the need to “advance the existence of a majority-French society in a Quebec where the future of French is assured,” this research project is an opportunity to shed light on the relationship that the ESCQ have with the French language in Quebec and official bilingualism in Canada as a whole. This is also an opportunity to explore how Quebec’s English-speaking minority can be considered as bridge-builders or even as a potential ally of the promotion of French in Canada as a whole, with a view to developing a more constructive discourse that better acknowledges their contributions and, ultimately, deconstructs certain misperceptions.
Keywords: Official Language Minority Community (OLMC)

Resolution 2024-01 : French Instruction Availability - Quebec Federation of Home and School Associations (QFHSA) (2024)

Women in Official Language Minority Communities - Quebec English-speaking Communities Research Network (QUESCREN); Canadian Institute for Research on Linguistic Minorities (2024)
Keywords: Official Language Minority Community (OLMC)

Report Card on French May Bring More Coercive Measures, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Brief to the Standing Committee on Official Languages : The Importance of the University Research Ecosystem for Quebec’s English-Speaking Official Language Minority Community - O'Donnell, Lorraine (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief calls for the Government of Canada to increase funding for research on Quebec’s English-speaking official language minority community (OLMC) and for the ecosystem in minority-language post-secondary institutions that is required for research production. The brief addresses the situation and needs, and proposes a solution.
Keywords: Official Language Minority Community (OLMC)

Portrait de l’évolution socioéconomique des Québécois et Québécoises d’expression anglaise - AppEco (Advisory Committee for English-speaking Quebecers (ACESQ), 2024)

English-language Health and Social Services Access in Québec : Comparison 2019-2023 - CROP (2024)

Socio-Demographic Profile of Québec's English-speaking Youth Aged 15-29 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This report profiles the situation of English-speaking citizens of Québec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for most Québecers aged 15-29, these milestones are: completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policymakers and program managers to public institutions, community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Québec’s citizens.

Network News - Quebec Community Groups Network (QCGN) (2024)

An Uphill Battle : Homelessness in Canada and Quebec and Its Likely Impact on the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Socio-Demographic Characteristics of Visible Minorities in Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Gatineau, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Laval, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Longueil, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in MRC de L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de L'Assomption.

Socio-Demographic Characteristics of Visible Minorities in MRC de La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de La Vallée-du-Richelieu.

Socio-Demographic Characteristics of Visible Minorities in MRC de Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Les Moulins.

Socio-Demographic Characteristics of Visible Minorities in MRC de Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Roussillon.

Socio-Demographic Characteristics of Visible Minorities in MRC de Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Thérèse-De Blainville.

Socio-Demographic Characteristics of Visible Minorities in MRC de Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Vaudreuil-Soulanges.

Socio-Demographic Characteristics of Visible Minorities in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec.

Socio-Demographic Characteristics of Visible Minorities in Québec City - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec City, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for the rest of Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Chaudière-Appalaches.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Abitibi-Témiscamingue.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Est-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Estrie – CHU de Sherbrooke.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Outaouais.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Capitale-Nationale.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Mauricie-et-du-Centre-du-Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Centre.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Est.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Ouest.

Socio-Demographic Characteristics of Visible Minorities in RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Lanaudière.

Socio-Demographic Characteristics of Visible Minorities in RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Laval.

Socio-Demographic Characteristics of Visible Minorities in RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS des Laurentides.

Socio-Demographic Characteristics of Visible Minorities in RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Bas-Saint-Laurent.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Sud-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Nord-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Saguenay - Lac-Saint-Jean

Socio-Demographic Characteristics of Visible Minorities in Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Sherbrooke, which is considered a territory equivalent to an MRC.

Network News - Quebec Community Groups Network (QCGN) (2024)

Developing Regulations for Part VII (Advancement of Equality of Status and Use of English and French) of the Official Languages Act - Official Languages Centre of Excellence Office of the Chief Human Resources Officer (2024)

Quebec Community Groups Network: The Official Languages Act - Quebec Community Groups Network (QCGN) (2024)

Brief for Consultations with the Secrétariat aux relations avec les Québécois d’expression anglaise - Seniors Action Quebec (SAQ) (2024)

Portrait of the Clientele : Qualitative Research - Advisory Commitee for English-Speaking Quebecers (2024)

Official Languages in Canada - Canada. Office of the Commissioner of Official Languages (2024)

The English Presence in Quebec - Canada. Office of the Commissioner of Official Languages (2024)

Community Netlink - Community Health and Social Services Network (CHSSN) (2024)

Highlights of the Sociodemographic Profile of English-speaking Quebecers Aged 15-19 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Abitibi-Témiscamingue - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Lanaudière - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Laval - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Laurentides - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Bas-Saint-Laurent - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

About the Réseau de l'Est de l'Île pour les Services en Anglais (REISA) Project - Community Health and Social Services Network (CHSSN); Réseau de l’est de l’île pour les services en anglais (REISA) (2024)

Annual Report 2023-2024 - Provincial Employment Roundtable (PERT) (2024)

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Capitale-Nationale’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues English-speaking workers in Capitale-Nationale face, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Chaudière-Appalaches’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Chaudière-Appalaches, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Côte-Nord - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Côte-Nord’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Côte-Nord, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Gaspésie–Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Gaspésie-Îles-de-la-Madeleine’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Gaspésie-Îles-de-la-Madeleine, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Montérégie - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Montérégie’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Montérégie, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Saguenay–Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Saguenay-Lac-Saint-Jean’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes by identifying some of the employment challenges and issues for English-speaking workers in Saguenay-Lac-Saint-Jean, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in the Laurentides - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Les Laurentides’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Les Laurentides, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Situation of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Educational Experiences and Outcomes of Black Youth in Quebec English-Language High Schools - Quebec English-speaking Communities Research Network (QUESCREN) (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by theSecrétariat aux relations avec les Québécois d’expression anglaise from December 2021to the present.
Keywords: Official Language Minority Community (OLMC)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by the Secrétariat aux relations avec les Québécois d’expression anglaise from December 2021 to the present. Founded in 1979, Townshippers’ Association is mandated to promote the interests ofthe ESC in the historical Eastern Townships, strengthening the cultural identity of thiscommunity, and encouraging the full participation of the English-speaking population in the community at large. Townshippers’ Association’s projects address heritage andculture, community development, access to health and social services, support for seniors, and youth retention. The Secretariat aux relations avec les Québécois d’expression anglaise is responsible forensuring that the concerns of English-speaking Quebecers are taken into account ingovernment orientations and decisions in collaboration with government ministries and bodies.

Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.

Déclaration commune en réponse à un rapport publié par Mario Beaulieu, député / Joint Statement in Response to Report Released by Mario Beaulieu, M.P. - English Language Arts Network (ELAN); Quebec Writers' Federation (QWF); Quebec Drama Federation (QDF); Association of English-language Publishers of Quebec (AELAQ) (2023)
Keywords: Official Language Minority Community (OLMC)

Pregnancy Outcomes in Anglophone Quebec : Recent Research Results - Auger, Nathalie (QUESCREN Lunch & Learn, 2023)

QCGN Statement on Bill 15 and Closure - Quebec Community Groups Network (QCGN) (2023)

Supporting the Economic Development of Québec’s English-Speaking Communities - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is pleased to submit this brief and present it to the Standing Committee on Official Languages to contribute to its study of the economic development of official language minority communities (OLMCs). We believe this is an important study, which we hope will shed light on the needs of our community and lead to the development of new government actions that address the economic development challenges in Québec’s English-speaking communities, particularly in employment and employability.
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

QFHSA Celebrates Successful Negotiations Regarding Sections of Bill 23 - Quebec Federation of Home and School Associations (QFHSA) (2023)

QCGN Statement on Bloc Québécois report on federal funding for Quebec’s English-speaking minority - Quebec Community Groups Network (QCGN) (2023)

Community Vitality & Acceptability of English Canadian Migrants Rated by Québecois Francophone, Acadian and Franco-Ontarian University Students - Bourhis, Richard Y.; Sioufi, Rana; Allard, Réal (QUESCREN Education and Vitality Forum 2023, 2023)

Minorities, Minoritization, and the Education of African, Black, and Caribbean Youth - Collins, Tya (QUESCREN Education and Vitality Forum 2023, 2023)

Socio-demographic Profile of the Population Aged 55 and Over : Province of Quebec - Pocock, Joanne (2023)

Je m’engage donc nous sommes : Améliorer la motivation à communiquer en français langue seconde grâce à l’engagement communautaire - Popica, Maria; Gagné, Philippe; Rouleau, Sylvain (QUESCREN Education and Vitality Forum 2023, 2023)

English-speaking Quebec and Minority Language Educational Rights : A Lost Opportunity? - Thompson, Stephen (QUESCREN Education and Vitality Forum 2023, 2023)
Keywords: Official Language Minority Community (OLMC)

QFHSA Board of Directors Shocked at CAQ Attack on McGill, Concordia, and Bishop's - Quebec Federation of Home and School Associations (QFHSA) (2023)

Press Release: New study reveals economic precarity and limit job supports for racialized communities and English-speaking immigrants in Québec. - Provincial Employment Roundtable (PERT) (2023)

Brief to the Senate Standing Committee on Official Language’s Study of Matters Relating to Minority-language Health Services - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Senate Standing Committee on Social Affairs, Science and Technology : Study on Bill C-35, An Act respecting early learning and child care in Canada - Quebec Community Groups Network (QCGN) (2023)

The Provincial Government Makes It Difficult to Offer Praise! - Quebec Federation of Home and School Associations (QFHSA) (2023)

Three Approaches to Writing School Programs with Official Language Minorities : Research Brief no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

August & September 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

A Snapshot of Poverty Among Québec’s English-speaking Communities - Provincial Employment Roundtable (PERT) (2023)
Québec is home to more than 1.2 million English speakers, representing 14.9% of the province’s population. Data from the 2021 Census of Canada indicates that English-speaking Quebecers occupy a more precarious economic position than their French-speaking counterparts, experiencing higher rates of poverty and unemployment and earning lower median incomes. Research conducted by PERT has highlighted some of the specific barriers and challenges English speakers face regarding labour market integration and retention in Québec, including lack of French-language training for the workforce, lack of English-language employability services, lack of English-language vocational training, and lack of wrap-around support services. These employment challenges impact English speakers' labour market outcomes and are associated with higher rates of poverty. Furthermore, many of these challenges, especially lack of wrap-around supports (e.g. housing or food security), can directly contribute to – and result from – poverty.

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)

Climate Anxiety Among English-Speaking Youth in Québec - Pettem, Alexandre; Rengel, Fernanda (2023)

Mapping Employment Supports for Québec's Racialized and Immigrant English-speaking Communities - Gagnon, Morgan; Kuzviwanza, Sta (Provincial Employment Roundtable (PERT), 2023)

June & July 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Press Release : New Report Highlights the Best Practices for French-language Education in Québec - Provincial Employment Roundtable (PERT) (2023)

QCGN deeply disappointed Canada's Official Language Act will contain references to Quebec's Charter of the French Language - Quebec Community Groups Network (QCGN) (2023)

Le QCGN clôture son assemblée annuelle, résolu à défendre haut et fort les droits des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2023)

QCGN Wraps Up Annual Meeting Resolved to be a Strong Voice for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Provincial Employment Roundtable : Québec and the rest: A survey of national and international approaches to adult language training - Kuzviwanza, Sithandazile; Holt, Cimminnee (Provincial Employment Roundtable (PERT), 2023)

Learning French as an Adult : A Review of Current Best Practices in Adult French-language Training in Québec - Provincial Employment Roundtable (PERT) (2023)
Learning French is a challenge for many linguistic minorities in Québec. Given the growing primacy of French in the province, learning French is increasingly a priority for individuals who face French-language barriers and seek to participate in broader Québec society and the labour market. Previous research by the Provincial Employment Roundtable has explored Québec’s adult French-language training ecosystem in order to understand the availability and accessibility of programs in the province. This research demonstrated that Québec’s adult French-language training framework is a patchwork of programs with varying availability and costs, as well as significant barriers to access for individuals depending on their regional location, immigration status, and employment status, among other eligibility criteria.

Senate Standing Committee on Official Languages (OLLO) : Study of C-13 An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2023)
The QCGN has participated in every step of the modernization of the Official Languages Act, beginning with Bill S-209; an initiative of this Chamber led by the Honourable Maria Chaput. English-speaking Quebec worked closely and in good faith with our Francophone counterparts in the rest of Canada, Ministers of Canadian Heritage and Official Languages and this Committee during its historic study to modernize the Act, beginning in 2017.

Seniors Action Quebec Presentation on Study Matters Relating to Minority-Language Health Services - Seniors Action Quebec (SAQ) (2023)

Press Release : The Unemployment Gap Between English Speakers and French Speakers in Québec has Doubled, New Census Data Reveals - Provincial Employment Roundtable (PERT) (2023)

English-language Health and Social Services Access in Québec - Community Health and Social Services Network (CHSSN) (2023)

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

Action Plan on Official Languages Offers Opportunities for Quebec's English Speaking Community - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

Seniors Action Quebec Brief : Vieillir et vivre ensemble, chez soi, dans sa communauté, au Québec (VVE) - Plan d’action 2024-2029 - Seniors Action Quebec (SAQ) (2023)

Access to Justice in English Project : Access to the Courts of Quebec in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

Make the Case Report : Access to Senior Care in English in Quebec : A research analysis of English language rights in Quebec health care and access to the SAPA program for English-speaking seniors in Quebec - Quebec Community Groups Network (QCGN) (2023)
This report discusses and details one of the AJEQ Project’s candidate issues of research: access to senior health care services in English in Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Federal Budget Includes New Money for Official-Language Minorities - Quebec Community Groups Network (QCGN) (2023)

QCGN Welcomes Quebec Budget Support for English-speaking Community - Quebec Community Groups Network (QCGN) (2023)

A Language Rights Regime for Federally Regulated Businesses? - Quebec Community Groups Network (QCGN) (2023)

Access to Justice in English Project : Access to Quebec government websites in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

The Resilience of the Vulnerable Minority English Education Sector During the COVID-19 Pandemic - Advisory Board on English Education (2023)
This brief describes the vulnerabilities experienced in Québec’s English education sector, specifically in elementary and secondary schools and adult education and vocational training centres. The brief’s findings and recommendations are derived from a review of the research and from a survey conducted by ABEE. This survey (see Appendix 1) focused on the six vulnerable areas identified in the CSE report: mental health and well-being; teaching, learning and evaluation; professional development and training; governance and administration; education funding and resources; access and equity. The survey was made available in both French and English and sent to English sector teachers, administrators, parents and students. A detailed analysis of its findings is available in this brief's Research, Findings and Analysis section.

February & March 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Rural Schools, Linguistic Identities, and Official Language Minority Rights : Insights from Rights Holder Parents in Quebec - Pattison-Meek, Joanne; Langevin, Andréanne (Working Paper, 2023)
There is considerable scholarly work examining the ways Quebec’s language policies regulate the language of instruction in schools. The current paper contributes to the existing literature by sharing the voices of 21 rights holder parents living in rural areas of Quebec and discussing the ways language of instruction policies influence their school choices and impact their children’s school experiences in rural contexts.

Mental Health in the Anthropocene : Climate Anxiety among Québec’s English-speaking Youth - Rengel, Fernanda; Pettem, Alexandre (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations of the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Les Québécois d’expression anglaise connaissent un taux de chômage plus élevé et gagnent moins que leurs homologues francophones - Provincial Employment Roundtable (PERT) (2023)

What is the Difference Between a Common and Official Language? - Quebec Community Groups Network (QCGN) (2023)

The QFHSA Strongly Supports Prime Minister Justin Trudeau's Request to the Supreme Court of Canada to Investigate the Possibility of Regulating the Use of the Notwithstanding Clause - Quebec Federation of Home and School Associations (QFHSA) (2023)

Law 96: College Instruction in the Minority Language - Rengel, Fernanda (Youth for Youth Québec (Y4Y Québec), 2023)
Bill 96, An Act respecting French, the official and common language of Québec, was proposed to the National Assembly on May 13, 2021. It was sponsored by Coalition Avenir Québec MNA, M. Simon Jolin-Barrette, who at the time served as Minister Responsible for the French Language1 (Assemblée Nationale du Québec). The bill proposed several amendments overhauling the Charter of the French language, colloquially known as Bill 101, which had received royal assent in 1977. The stated purpose of Bill 96 was a renewed focus on strengthening the use of French–Québec’s sole official language– in all spheres of public life. Among other elements, the bill involves establishing francization frame- works in the workplace, as well as specifying Québec’s role in expanding and promoting francophone and Acadian communities, both within Canada and abroad (Bill 96 3). The bill received royal assent on June 1st, 2022, becoming Law 96. Being considered in this brief are Law 96’s amendments to the 1977 Charter of French with regard to college instruction in English. These impose certain expectations and limitations on college-level instruction in the minority language as the Charter did to primary and secondary instruction in the minority language in 1977.

What is the Difference Between a Common and Official Language? - Quebec Community Groups Network (QCGN) (2023)

Brief to the Pre-Budget Consultation Chaired by Finance Minister Eric Girard - Quebec Community Groups Network (QCGN) (2023)
Sections A to C of this brief address the funding needs of Quebec’s community sector organizations, and more specifically the needs of those organizations which provide services and programs to English-speaking Quebecers. The Quebec Community Groups Network (QCGN) has long held a mandate to collect, collate, and articulate the needs of Quebec’s English-speaking community, and the work that we have done on this file in recent years has informed these sections of our brief significantly.

Producing Regulations for Part VII of the Official Languages Act : English-speaking Quebec’s Stake in the Process - Quebec Community Groups Network (QCGN) (2023)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)

Impact Report 2022-2023 - 4Korners (2023)

Annual Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)

CHSSN À propos de Nous / Who We Are - Community Health and Social Services Network (CHSSN) (2023)
Through a program called the Networking and Partnership Initiative (NPI), the CHSSN supports 23 community organizations serving English-speaking communities across the province in their efforts to collaborate with partners to improve access to health and social services in English (see map).

Community Mobilization Model for Improving Health and Well-being of English-speaking Communities in Quebec - Community Health and Social Services Network (CHSSN) (2023)

Community Mobilization Model : For improving the health and well-being of English-speaking communities in Quebec - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Investing in the vitality of English-speaking Quebec - Community Health and Social Services Network (CHSSN) (2023)

Networking and Partnership Initiative / Initiative de réseautage et de partenariat (NPI) - Community Health and Social Services Network (CHSSN) (2023)

Annual Report 2022-2023 - English Speaking Catholic Council (2023)

2023 Report : "An Analysis of the Demographic and Socio-Economic Characteristics of Quebec's English-Speaking Community Compared to the French-Speaking Population" with a Focus on the RTS de la Montérégie-Oues - Montérégie West Community Network (MWCN) (2023)

Annual Report : 2022-2023 - NDG Community Council (NDGCC) (2023)

Demographic Profiles of Québec's English-speaking Communities of Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities of Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities, Quebec - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Abitibi-Témiscamingue and MRC Abitibi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Centre-du-Québec and MRC Arthabaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and Lévis - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Beauce-Sartigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Bellechasse - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC La Nouvelle-Beauce - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Les Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Lotbiniére - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Côte-Nord and MRC Caniapiscau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Côte-Nord and MRC Le Golfe-du-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and les Îles-de-la-Madeleine - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC Avignon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC Bonaventure - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC La Côte-de-Gaspé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC Le Rocher Percé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and Mirabel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Antoine-Labelle - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Argenteuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Les Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Maurice and la Tuque - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Montérégie and Longueuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Outaouais and Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Outaouais and MRC La Vallée-de-la-Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Outaouais and MRC Les Collines-de-l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Chaudière-Appalaches - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Outaouais - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Capitale-Nationale - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Côte-Nord - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Gaspésie - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Centre - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Est - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Ouest - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Îles - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Laurentides - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Brief : Public Consultation on the Government Action Plan to Combat Poverty and Social Exclusion - Provincial Employment Roundtable (PERT) (2023)
Québec is home to more than 1.2 million English speakers, representing 14.9% of the province’s population. Data from the 2021 Census of Canada indicates that English-speaking Quebecers occupy a more precarious economic position than their French-speaking counterparts, experience higher rates of poverty and unemployment and earn lower median incomes. Research conducted by PERT has highlighted some of the specific barriers and challenges English speakers face regarding labour market integration and retention in Québec, including lack of French-language training for the workforce, lack of English-language employability services, lack of English-language vocational training, and lack of wrap-around support services. These employment challenges impact English speakers' labour market outcomes and are associated with higher rates of poverty.1 Furthermore, many of these challenges, especially the lack of wrap-around supports (e.g. housing or food security), can directly contribute to – and result from – poverty.

Census 2021 Update : A Brief Review of the Latest Data on Employment Among Québec’s English Speakers - Provincial Employment Roundtable (PERT) (2023)
A review of the most recent census data on the employment situation of Québec’s English-speaking communities reveals that English speakers continue to experience significant challenges in Québec’s labour market. Despite a high rate of labour force participation and increases in educational attainment, English speakers in most regions of Québec face higher unemployment rates, lower median incomes and higher rates of poverty compared to the French-speaking majority. This report provides an overview of key labour market characteristics for Québec’s English-speaking communities based on data from the 2021 Census.

Disparities in Mental Health and Its Determinants Among Quebec High School Students by Language of Instruction - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Disparities in Mental Health and Its Determinants Among Quebec High School Students by Language of Instruction - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Resolution 2023-07 : Ensure the Availability of Bilingual Services by Student Ombudsmen - Quebec Federation of Home and School Associations (QFHSA) (2023)

English Eligibility Certificates : Information about How to Apply for a Certificate and Who Is Eligible to Attend English Schools in Québec - Regional Development Network (RDN) (2023)

Annual Report - Réseau de l’est de l’île pour les services en anglais (REISA) (2023)

Annual Report - Voice of English-speaking Quebec (VEQ) (2023)

Charting the Course : 2022-2023 Year in Review - Youth for Youth Québec (Y4Y Québec) (2023)

People's History of English-speaking Quebec : A Linguistic Minority Community Vitality Project - O'Donnell, Lorraine; Donovan, Patrick (Association of Critical Heritage Studies Biennial Conference, 2022)

French-speaking Quebecers Strongly Support Right of English-speaking Citizens to Obtain Government Services in English – Poll - Quebec Community Groups Network (QCGN) (2022)

Consensus on Language Issues in Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (2022)

Most Quebecers, English and French, Want Ottawa to Protect Rights of English-speaking Quebecers : Poll - Quebec Community Groups Network (QCGN) (2022)

New Official Languages Act Must Safeguard the Minority Language Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN Welcomes Senate Report that Calls for Equality of French and English Language Rights - Quebec Community Groups Network (QCGN) (2022)

QCGN Urges Parliamentarians to Guarantee Future of English-speaking Quebec as Equal Partner in New Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

QCGN Congratulates Eric Girard, New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN Members Strongly Endorse Battle Against Laws and Policies Eroding the Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Premier's Re-election Provides Opportunity for a Fresh Start : QCGN Calls for Appointment of a Dedicated Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Brief to the House of Commons Standing Committee on Official Languages on the Topic of Bill C-13, an Act To Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses and to Make Related Amendments to Other Acts - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
The present brief focuses on the first purpose, Bill C-13 amendments to the OLA. This is the topic on which I in my role as research associate at the Quebec English-Speaking Communities Research Network (QUESCREN) have developed the most knowledge.

Brief to the House of Commons Standing Committee on Official Languages - Provincial Employment Roundtable (PERT) (2022)
The Provincial Employment Roundtable is pleased to submit this brief to the House of Commons Standing Committee on Official Languages regarding Bill C-13, An Act to amend the Official Languages Act, to enact the Use of French in Federally Regulated Private Businesses Act and to make related amendments to other Acts. This brief outlines the context for the English-speaking communities in Québec, particularly with respect to the significant employment and employability challenges they face. It also provides comments and recommendations for Bill C-13 with the goal of strengthening the Official Languages Act (the ‘OLA’) and supporting the development and vitality of Québec’s English-speaking communities.

Modernizing the Official Languages Act : How the Federal Government Got it Wrong with C-13 - Quebec Community Groups Network (QCGN) (2022)

Vocational and Technical Training Programs Offer Pathways to French-language Acquisition for Québec’s English Speakers - Provincial Employment Roundtable (PERT) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

September 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

Legislative Brief to House of Commons and Senate Standing Committee(s) on Official Languages : Bill C-13, An Act to amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to other Acts (short title: An Act for the Substantive Equality of Canada’s Official Languages) - Task Force on Linguistic Policy (2022)
The TFLP submits that Bill C-13, the proposed modernization of the Official Languages Act (“OLA”), redefines and restructures Canada’s federal Official Languages framework in fundamental and, likely, undesirable ways. It introduces an unprecedented asymmetrical approach to the protection and promotion of Official Languages in Canada and, perhaps even more problematically, to the defence of the linguistic rights and recourses afforded to French speakers and English speakers, both in the Province of Québec, and across the country.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Stay Granted in First Court Challenge to Bill 96 - Quebec Community Groups Network (QCGN) (2022)

Linguistic Diversity and Use of English and French in Canada : 2021 Census of Population - Quebec Community Groups Network (QCGN) (2022)

Civic Engagement Motivations and Barriers for English-Speaking Quebec Youth - Nykoluk, Brock (2022)
As such, to better understand Québec’s civic land- scape, civic engagement for ESQY ought to receive more scholarly attention. This report aims to help fill this gap by answering the following questions: How do ESQY characterize the motivations behind their civic engagement? How do ESQY characterize the barriers that hinder their civic engagement?

The Importance of the University Research Ecosystem for Quebec's English-speaking Official Language Minority Community - O'Donnell, Lorraine (Quebec English-Speaking Communities Research Network (QUESCREN), 2022)
This brief calls on the upcoming federal Action Plan for Official Languages to enhance support for research on Quebec’s English-speaking official language minority community (OLMC) and for what we call the “ecosystem” required for the production of this research. As such, the brief addresses the following guiding principle of the Action Plan consultations, as stated on the official website: “to strengthen our support in order to foster the development of Canada’s rich and numerous official language minority communities.”
Keywords: Official Language Minority Community (OLMC)

Lack of French-Language Training Opportunities for Professional Orders Contributes to Labour Market Shortage - Provincial Employment Roundtable (PERT) (2022)

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

Partners in Health - Centre for Access to Services in English (CASE) (2022)

List of Employers in Quebec City Region with Jobs That Require English Skills - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

41st Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2022)

QCGN Has New Interim President and Renewed Resolve to Battle Bill 96 and Other Legislation Detrimental to English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN Proposes Major Amendments to Federal Bill Modernizing the Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Report on the Education and Vitality Forum : Overview - Macris, Antonia; QUESCREN (2022)

National Assembly Adopts Bill 96 - Quebec Community Groups Network (QCGN) (2022)

Statement by The Honourable Marlene Jennings, P.C. President of the Quebec Community Groups Network on the Adoption of BIll 96 - Quebec Community Groups Network (QCGN) (2022)

Newsletter - English Parents' Committee Association (EPCA) (2022)

Brief to House of Commons Standing Committee on Official Languages : Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2022)
The Official Languages Act is a lifeline for English-speaking Quebec. With Quebec’s Bill 96, the community needs this lifeline more than ever. But with Bill C-13, this lifeline is fraying. Founded in 1995, the Quebec Community Groups Network (“QCGN”) is a not-for-profit organization linking English-language community organizations across Quebec. The QCGN—like the community it serves—is proud to support the protection and promotion of the French language in Canada. The QCGN advocates for linguistic duality in every province and territory. The English-speaking minority in Quebec is a diverse, bilingual, and resilient community that is facing serious economic challenges—in the face of persistent myths and stereotypes. Although the English language itself is not threatened, the English-speaking community’s challenge is in maintaining the community’s vitality and survival in all regions of Quebec.
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2022)

Educational Vitality of the English-speaking Communities of Quebec : From Bill 101 to Bill 96 and Some Ideological Clarifications - Bourhis, Richard Y. (Coalition for the Future of English Education, 2022)

Committee Concludes Examination of Bill 96 : CAQ Enshrines Primacy of French Language and "Quebec Nation" Over Canadian and Quebec Human Rights Charters - Quebec Community Groups Network (QCGN) (2022)

Statement on Coalition Avenir Québec Government’s Refusal to Budge on Provisions for English-speaking CEGEP Students - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Committee Adopts Series of Surprise Changes Regarding Bilingualism in Quebec Judicial Appointments - Quebec Community Groups Network (QCGN) (2022)

QFHSA News Bulletin : Statement on the Coalition Avenir Quebec's Refusal to Budge on Provisions for English-speaking CEGEP Students - Quebec Federation of Home and School Associations (QFHSA) (2022)

Statement on the Coalition Avenir Quebec's Refusal to Budge on Provisions for English-speaking CEGEP Students - Quebec Federation of Home and School Associations (QFHSA) (2022)

Committee Substantively Changes Quebec Human Rights Laws - Quebec Community Groups Network (QCGN) (2022)

Committee Adopts Proposed Changes to Civil Code of Quebec - Quebec Community Groups Network (QCGN) (2022)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Activity Report : A Year In Review 2021-22 - Literacy Quebec (LQ) (2022)

Committee Debates New Complaints Procedures for the Office Québécois de la langue française - Quebec Community Groups Network (QCGN) (2022)

Committee Discusses Creation of Francisation Québec and a Ministry of the French Language - Quebec Community Groups Network (QCGN) (2022)

Committee Discusses Use of French Within Businesses - Quebec Community Groups Network (QCGN) (2022)

Committee Discusses Quality of French Taught to Newcomers and English-speakers - Quebec Community Groups Network (QCGN) (2022)

Committee Closes Debate on CEGEPS and Turns to Universities - Quebec Community Groups Network (QCGN) (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

Committee Continues Debate on the Future of English-language CEGEPS - Quebec Community Groups Network (QCGN) (2022)

The Best-Treated Minority in the World : Historical and Discursive Analysis of a Cliché - Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Politicians, polemicists, and others have long referred to Quebec’s Englishspeaking community as the “best-treated minority in the world.”1 This loaded phrase has also been used to describe other minorities: French speakers within Canada as a whole, Indigenous peoples in Canada, and religious groups and minorities in many European and colonial contexts. Through a historical overview and discourse analysis, this paper traces how the phrase has been used and abused, justified, and criticized over time. The particular focus is the Quebec context. There, we see a shift from a largely consensual use of the phrase across all language groups to one that becomes increasingly divisive and problematic from the 1980s on. This shift parallels the English-speaking community’s evolving sense of itself as a minority in decline.
Keywords: Official Language Minority Community (OLMC)

March 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

The Community Liaison Model : Improving Access to Health and Social Services to Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2022)
This report explores the role of community liaison work in improving the health and wellbeing of individuals and communities who face barriers in their access to public healthcare services. Of specific focus is the CHSSN liaison model as a promising community-based response to reducing the linguistic and cultural barriers experienced by Quebec’s Englishspeaking communities.
Keywords: Official Language Minority Community (OLMC)

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Committee Continues Discussions Regarding Restrictions on CEGEP Admissions - Quebec Community Groups Network (QCGN) (2022)

Future Restrictions for Admissions to English-language CEGEPs Scruitinized - Quebec Community Groups Network (QCGN) (2022)

Committee Begins Examination of Language Restrictions Governing CEGEP Admissions - Quebec Community Groups Network (QCGN) (2022)

Understanding the Long-term Care Experience of Official Language Minorities in Canada: An Environmental Scan - Hsu, Amy T.; Ménard, Alixe; Scott, Mary (2022)
Members of minority and racialized communities across Canada commonly experience disparities in health and healthcare. In the context of the COVID-19 pandemic, minority and racialized individuals have been found to report poorer health outcomes and added barriers to healthcare access. While there is growing understanding of the impact of COVID-19 on individuals who live and work in residential long-term care (LTC) homes and other congregate care settings, little attention has been directed at examining inequities in the care experience and care-related outcomes that equity-seeking groups, including Official Language Minority Communities (OLMC), face within LTC. It’s clear that there is a need for systemic change within LTC; the pandemic, especially in its first two waves, highlighted several pre-existing issues within this sector. To ensure high-quality and equitable care for all aging Canadians, these system-level changes must be informed by evidence.
Keywords: Official Language Minority Community (OLMC)

Committee Examines Language Rules Governing Business and Public Education - Quebec Community Groups Network (QCGN) (2022)

English-speaking Québecers Experience Higher Unemployment and Earn Lower Incomes than their Francophone Counterparts - Provincial Employment Roundtable (PERT) (2022)

Committee Discusses Use of French in Professional Orders and the Workplace - Quebec Community Groups Network (QCGN) (2022)

Committee Examines Effects of Agency Directives on Quebec Immigrants - Quebec Community Groups Network (QCGN) (2022)

Committee Continues to Carve Out Exceptions to Exemplary Use of the French Language - Quebec Community Groups Network (QCGN) (2022)

More English-speaking Quebecers Reject Divisive ‘Historic Anglo’ Approach - Quebec Community Groups Network (QCGN) (2022)

Exemptions to the Use of French by Government Under Scrutiny by Committee - Quebec Community Groups Network (QCGN) (2022)

Bill 96 - National Assembly Committee Debates "Historic Anglo" Clause - Quebec Community Groups Network (QCGN) (2022)

Language Rights Under Health Act Will Not be Tied to 'Historic Anglophone' Definition - Quebec Community Groups Network (QCGN) (2022)

The Effects of the Pandemic on the Arts & Creative Sector in Québec : How Anglophone Artists, Creators, and Performers are Faring in a Time of Adversity - Eraso, Cecilia (Youth for Youth Québec (Y4Y Québec), 2022)
The arts, entertainment, and recreation sector is infamous for being in a state of constant flux. The experience of consecutive short-term contracts and annual seasonal employment terminations is a familiar reality for many creators, producers, and performers in Québec (Jeannotte, 2021). What is unique for some Québec artists is the experience of a linguistic divide in the provincial arts sector. In 2016, English-speaking artists in the province earned less than their Francophone counterparts, on average, making a median income of “85 cents for every $1 made by Francophone artists’’ (Hill, 2020). On the national level, statistics from the 2016 Canadian Census show that Anglophone artists from Québec have a lower median income than the rest of Canadian artists. These findings are especially surprising when considering that, nationally, English-speakers in Québec represent a significant portion of Canadian artists. Anglophones in Québec account for 4.6% of all Canadian artists, despite only representing 2.8% of the Canadian labour force (Hill, 2020). The data indicate that two factors, occupation and language, are related to discrepancies in income levels in Québec.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Legault Government Must Backtrack on Dawson Decision: QCGN - Quebec Community Groups Network (QCGN) (2022)

QESBA Deplores the Blatant Disregard for the English Education Community Following the Nomination of a New Assistant Deputy Minister - Quebec English School Boards Association (QESBA) (2022)

Quietly Adopted Regulation Could Hurt Quality of Health Care for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Report on the Health and Social Services Priorities of English-speaking Communities in Quebec - Carter, James; Pocock, Joanne; Health and Social Services Priorities Committee (Community Health and Social Services Network (CHSSN), 2022)
In the upcoming months, the federal government will announce the renewal of the Action Plan for Official Languages for the period 2023-2028. It will affirm Canada’s commitment to promote linguistic duality and the vitality of official language minority communities including Quebec’s English-speaking communities. As part of the federal commitment, Health Canada will be invited to develop a new Official Languages Health Contribution Program to improve access to health and social services for English-speaking communities in Quebec, and French-speaking communities in the rest of Canada.

Socio-demgoraphic Characteristics of Visible Minorities in Quebec's English-speaking Communities : 2016 Census Data - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2022)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for the province of Quebec and its RTS regions. It provides a 2016 baseline and point of comparison for the upcoming Statistics Canada release of census findings gathered during the COVID-19 pandemic.

The Black Community Resource Centre Presents : The Infographic Series : Demographics of Quebec's English-speaking Black Population - Black Community Resource Centre (BCRC) (2022)

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2022)

Exploring the Effects of Language as a Barrier on Access to Care Service Utilization and Well-being Outcomes for English-speaking Families in Quebec - Community Health and Social Services Network (CHSSN) (2022)
The majority of English speakers in Quebec, and parents to a child aged 0-8 years old, reported feeling socially awkward, uncomfortable and experiencing symptoms associated to stress and anxiety when speaking in French. Parents also reported feeling socially inhibited, and confused when required to speak in French to healthcare professionals. The qualitative interview also validated the existence of challenges navigating the healthcare system due to language barriers. Reported language barriers included difficulty communicating with professionals in French affecting their ability to access timely healthcare, compromised quality of patient care, and experiencing discrimination when requesting the provision of English services. Patients with lived experience pleaded the case that health policymakers had to act in order to ensure more equitable access to care and implement measures to better support English speakers (i.e., using Al and other technologies for booking).

Outil de référence pour venir en aide aux enfants et aux familles d’expression anglaise vulnérables / Reference Tool for Reaching Vulnerable English-speaking Children and Families - Community Health and Social Services Network (CHSSN) (2022)

Survey Highlights on the Vulnerability of English-speaking Fathers - Community Health and Social Services Network (CHSSN) (2022)

Survey on Vulnerability in the Context of Fatherhood : Preliminary Report - Community Health and Social Services Network (CHSSN) (2022)
The Regroupement pour la Valorisation de la Paternité (RVP) brings together more than 250 organizations and individuals from the 17 administrative regions of Quebec. Its mission is to value the role of fathers and to promote their importance in the family and in society for the development and well-being of children, in a perspective of equality between parents. The RVP has enlisted the services of SOM to consult Quebec fathers of children under 18 years of age in order to better understand the concept of vulnerability in the context of fatherhood, particularly from the perspective of the diversity of parental experiences and pathways. In partnership with the Community Health and Social Services Network (CHSSN), this report was based on a subsample of 400 respondents who completed the questionnaire in English.

Youth Pulse Check Survey : Key Findings - Community Health and Social Services Network (CHSSN) (2022)

Working Together for a More Vital Community : The 2022-2027 Community Developmet Plan for English-speaking Quebec - Community Vitality Roundtables (Quebec Community Groups Network (QCGN), 2022)
The community sector serving English-speaking Quebec cultivates a sustained, ongoing capacity to collect, analyze, and share information (qualitative and quantitative) necessary to more deeply understand our community.

French-language Support for Québec's English-speaking Professionals - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
French-language barriers can be a challenge for professionals who are English speakers and must practice their profession in accordance with French-language policies. Despite high levels of English-French bilingualism among Québec’s English speakers, French remains a challenge for some who require additional profession-specific French-language training. Not only is French-language proficiency a requirement for membership in Québec’s professional orders, but professionals who do not meet language criteria must also pass a French-language competency exam administered by the Office québécois de la langue française (OQLF). Additionally, professional orders can mandate all their members to take French-language professional competency exams throughout their careers.

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)

Monteregie West Healthcare Information Booklet for English Speakers - Montérégie West Community Network (MWCN) (2022)

Society Pages - Morrin Centre (2022)

Society Pages - Morrin Centre (2022)

Youth Pulse Check : Survey Results Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

2021 Employment Survey of English-speaking Quebecers and Organizations - Provincial Employment Roundtable (PERT) (2022)
This report explores the employment experiences of English speakers in Québec as well as the issues and needs they face when it comes to navigating the labour market. English-speaking Quebecers, who are Québec’s official language minority community, sit at the intersections of various identities and communities from which diverse challenges and opportunities arise. At the same time, there are shared experiences of being an English speaker in Québec. One of them is the socioeconomic status of the English-speaking community as a whole. Despite the historical position of English speakers as a socioeconomic elite in Québec, today’s English-speaking community is collectively characterized by higher unemployment rates and lower incomes when compared to the French-speaking majority.

Bill 96 & Employment of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
On May 24, 2022, Québec’s National Assembly passed Bill 96, An Act Respecting French, the Official and Common Language of Québec. The bill, which presents significant modifications to The Charter of the French Language (Bill 101), as well as other existing legislation, was passed more than a year after it was introduced. On June 1, 2022, Bill 96 received royal assent and some of its clauses came into effect immediately. Other clauses of the bill will come into effect at later dates.

Employment Profile of English Speakers in Abitibi-Témiscamingue - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Abitibi-Témiscamingue’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Abitibi-Témiscamingue’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Bas-Saint-Laurent - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Bas-Saint-Laurent’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Bas-Saint-Laurent’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Capitale-Nationale’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Capitale-Nationale’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Centre-du-Québec - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Capitale-Nationale’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Capitale-Nationale’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Chaudière-Appalaches’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Chaudière-Appalaches’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Côte-Nord - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Côte-Nord’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Côte-Nord’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Estrie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Estrie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Estrie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Gaspésie-Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by GaspésieÎles-de-la-Madeleine’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Gaspésie-Îles-de-la-Madeleine’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Lanaudière - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Lanaudière’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Lanaudière’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Laurentides - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by English-speaking communities in the Laurentides by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys the economic structure of the Laurentides, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Laval - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Laval’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Laval’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Mauricie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Mauricie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Mauricie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Montérégie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Montérégie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Montérégie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Montréal - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Montréal’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Montréal’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Nord-du-Québec - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Nord-du-Québec’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Nord-du-Québec’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Outaouais - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Outaouais’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Outaouais’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
A review of available data on the employment status of English speakers in Québec reveals that English speakers — who represent 13.8% of Québec’s population and 14.3% of its labour force — face considerable challenges in the labour market. English speakers in most regions of Québec have higher unemployment rates and lower aftertax median incomes compared to French speakers, who represent 85.3% of the population.

Employment Profile of English Speakers in Saguenay-Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Saguenay-Lac-Saint-Jean’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Saguenay-Lac-Saint-Jean’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

English-Language Vocational and Technical Training in Québec - Provincial Employment Roundtable (PERT) (2022)
In recent years, there has been a renewed interest in the role of vocational and technical training in meeting urgent labour market needs, as well as the broader economic and social benefits it provides to individuals and societies. Vocational and technical training (VTT), which aims to equip students with hands-on skills for direct entry into the labour market, is offered at the secondary and college level in Québec. The majority of Québec’s VTT programs are offered in French and primarily serve the French-speaking majority in Québec, who represent 85.3% of the province’s population. There is a smaller ecosystem of English-language VTT programs, which are offered primarily to Québec’s English speakers, who account for 13.8% of the population.

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

C-13 An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to Other Acts - Quebec Community Groups Network (QCGN) (2022)

Annual Report - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

English : an Asset! - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

2021-2022 Annual Report - The English Speaking Catholic Council (2022)

Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

Opposition Grows to Restrictive Definition of English-speaking Community - Quebec Community Groups Network (QCGN) (2021)

The Importance of Resurrecting English-speaking Healthcare Services in Québec - Jackson-Cappuccino, Ella (Youth for Youth Québec (Y4Y Québec), 2021)
French is the first language of 71.2% of Quebecers. For the remaining 27.9%, communication outside of this language can be difficult, especially in regard to health care (Ouimet et. al 3).This is of concern as those who seek medical attention or health resources may not be provided adequate care given the linguistic barrier. Particularly, it is Québec’s Englishspeaking minority that is most affected by this issue (Ouimet et. al 3). Within this minority, there are still hundreds of thousands of English-speaking individuals who desire to seek health services in their first official language. The wish does not simply arise due to a lack of bilingualism. Evidence shows that in times of crisis - when individuals look to communicate a matter of importance - they most often revert to their mother tongue (Silver 686). Without resources designed to cater to the English-speaking population, the government subjects this linguistic minority group to unequal health care services.

Network News - Quebec Community Groups Network (QCGN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

QCGN Eager to Work on Modernization of Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Executive Summary of Task Force Legislative Brief on Bill 96, An Act Respecting French, the Official and Common Language of Qu(e)ébec - Task Force on Linguistic Policy (2021)
The Task Force on Linguistic Policy (“Task Force”) submits that Bill 96, the proposed modernization of the Charter of the French Language, redefines and restructures Quebec’s and Canada’s legal structure in fundamental and illegitimate ways. It institutes the primacy of the French language above all other considerations in law and governance. This linguistic re-engineering is incompatible with individual rights, natural justice, human and civil rights, national unity and a bilingual country.

On the Planned Decline of English Education in Quebec, Bill 96 and Some Ideological Clarifications - Bourhis, Richard Y. (Education and Vitality Forum, 2021)

QUESCREN's Education Research Briefs - Horrocks, Debbie; Legault, Emma (Education and Vitality Forum, 2021)

Opposition Grows to Premier’s Pigeonholing of ‘Historic Anglos’ - Quebec Community Groups Network (QCGN) (2021)

Allocation dans le cadre du Forum de QUESCREN sur l'éducation et la vitalité - Théberge, Raymond (2021)

QCGN to Air Canada : Apology Alone Cannot Undo Damage to English-speaking Quebec - Quebec Community Groups Network (QCGN) (2021)

Comparing Unemployment Rates Among Québec's English and French Speakers by Education Level - Dufour, Caroline (Education and Vitality Forum, 2021)

Report on the Education and Vitality Forum - Macris, Antonia; O'Donnell, Lorraine; Shoumarova, Lina; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
From November 3 to 5, 2021, researchers, practitioners, community stakeholders, and policy makers from across Quebec gathered virtually for a three-day event entitled Education and Vitality Forum: Supporting English-Language Minority Education in Quebec. This was the second forum convened by the Inter-Level Educational Table (ILET), a committee of the Quebec English-Speaking Communities Research Network (QUESCREN) at Concordia University. Its objective was to encourage mobilization around the development of a healthy and sustainable English-language educational offer in Quebec that supports student retention, access to good jobs in the province, and a strong sense of identity and belonging. This report provides an overview of the Forum and key takeaway messages from it
Keywords: Official Language Minority Community (OLMC)

Mapping Quebec's English-Speaking Population and English-Language Schools - Springate-Floch, D'Arcy (Education and Vitality Forum, 2021)

Community Development Plan 2022-2027 : Roundtable - Quebec Community Groups Network (QCGN) (2021)

Reisaction Newsletter : no. 30 - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Hats and High Tea : Local Collector to Share "Mobile Museum" in Bilingual Talk Highlighting the History of Fashion from 1940-1965, Followed by a Traditional English-style High Tea - Centre for Access to Services in English (CASE) (2021)

Gun Violence in Montréal : Context, Causes, Reactions, and Recommendations - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2021)
Montréal has recently been experiencing an unprecedented spike in gun violence, primarily perpetrated by a younger demographic. These shootings are occurring more frequently in broad daylight, in the midst of populated urban areas (Magder). As of August 31, the Montréal police (the SPVM) had documented 77 separate firearms being discharged, with 360 bullets being fired in roughly 100 shootings. This has already surpassed total instances for 2019 and 2020. 654 firearms have been seized, furthermore, the highest ever for the SPVM. This has led to 23 homicides, which is already rapidly approaching the 25 that were observed in both 2019 and 2020 (Perron).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Dear Mr. Premier : English-speaking Quebecers are full-fledged, contributing members of Quebec society - Quebec Community Groups Network (QCGN) (2021)

QCGN Eager to Collaborate with New Official Languages Minister Ginette Petitpas Taylor - Quebec Community Groups Network (QCGN) (2021)

Bill 96 is Profoundly Flawed and Must be Withdrawn - Quebec Community Groups Network (QCGN) (2021)

Strategic Intervention Plan : English Federal Correctional Services in Quebec - Quebec Community Groups Network (QCGN) (2021)

Task Force Legislative Brief on Bill 96, An Act Respecting French, the Official and Common Language of Qu(e)ébec - Task Force on Linguistic Policy (2021)
The Task Force on Linguistic Policy (Task Force) was formed by concerned citizens toadvocate against the Government of Canada’s “White Paper” and Bill C-32 and the Government of Quebec’s Bill 96 and the proposed Constitutional amendment. The “White Paper” and Bill C-32, Bill 96 and the proposed Constitutional amendment, taken as a whole, are a fundamental restructuring of the Canadian constitution, language policy and our basic human rights and freedoms.

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Data Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Funding Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Environmental Scan Report : Organization and Network Health Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Environmental Scan Report : Representation Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.

Resolution on the Definition of Quebec's English-speaking Community / Résolution concernant la définition de la communauté d'expression du Québec - Quebec Community Groups Network (QCGN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Opening Remarks by QCGN President, the Honourable Marlene Jennings, P.C., LLB to the Committee on Culture and Education : Special Consultations and Public Hearings on Bill 96, an Act Respecting French, the Official and Common Language of Quebec - Jennings, Marlene (2021)

Brief to the National Assembly Committee on Culture and Education : Special Consultations and Public Hearings on Bill 96, an Act Respecting French, the Official and Common Language of Quebec - Quebec Community Groups Network (QCGN) (2021)
In this brief, the QCGN articulates three sets of concerns: first, Bill 96 fundamentally alters the Quebec state, which is of concern to all Quebecers. Second, Bill 96 will make it harder to do business in Quebec, which is also of concern to all Quebecers. Third, Bill 96 will have adverse impacts on the 1.1 million Quebecers who belong to the English-speaking minority. The QCGN supports the policy goal of promoting the French language in Quebec, but suggests there are other ways to achieve this goal in an inclusive manner, to the benefit of all Quebecers.

QCGN Urges Quebec Government to Backtrack on Bill 96 - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Congratulates Parties for Federal Election - Quebec Community Groups Network (QCGN) (2021)

Open Letter to Minister Simon Jolin-Barrette from Marlene Jennings - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Urges English-speaking Quebecers to Vote for Best Local Candidate - Quebec Community Groups Network (QCGN) (2021)

Closing Remarks of Kevin Shaar, Vice-President of QCGN, to QCGN Hearings on Bill 96 - Shaar, Kevin (2021)

Willingness of Quebec-born Anglophone and Francophone Students to Stay in Quebec or Leave - Bourhis, Richard; Sioufi, Rana (QUESCREN 'Lunch & Learn' Series, 2021)

Federal Candidates Fail to Respond to Questionnaire on Linguistic Policy - Task Force on Linguistic Policy (2021)

Brief on Bill 96 : An Act Respecting French, the Official and Common Language of Quebec - Neal, Christopher; Barlow, Julie; Rodgers, Guy; Maturo, Nick (English-Language Arts Network (ELAN), 2021)

Brief on Bill 96 : An Act Respecting French, the Official and Common LAnguage of Quebec Submitted by the Quebec Writers' Foundation (QWF), The English Language Arts Network (ELAN), and the Quebec Drama Federation (QDF) - Quebec Writers' Federation (QWF); English Language Arts Network (ELAN); Quebec Drama Federation (QDF) (2021)
As part of Quebec’s English-speaking community, as artists, storytellers, dramatists and performers embedded in and contributing to Quebec’s cultural life, we are deeply troubled by the character, spirit and content of Bill 96, and the negative impact it threatens to have on Quebec’s English-language arts community.

Opening Remarks of Marlene Jennings, President of QCGN, to QCGN Hearings on Bill 96 - Jennings, Marlene (2021)

Statement on Bill 96 : An Act Respecting French, the Official and Common Language of Quebec - The English Speaking Catholic Council (ESCC) (2021)

Statement on Bill 96 by the Board of Directors of the Quebec Federation of Home and School Associations Inc. (QFHSA) - Quebec Federation of Home and School Associations (QFHSA) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

QCGN Organizes Parallel Bill 96 Consultation - Quebec Community Groups Network (QCGN) (2021)

QCGN Calls on Federal Parties and Candidates to Support the Language Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2021)

Black in Quebec Presents : In Focus - Davids, John; Fang, Xiaoyan (Black Community Resource Centre (BCRC), 2021)
Due to the Information Gaps pertaining to the well-being of the ESBC, the project collected detailed, qualitative information from members of Quebec's ESBC through conducting Focus Groups. These were meant to better inform the project about different aspects of the community such as the challenges facing the ESBC and solutions which should be considered. This process occurred in two parts, one-on-one interviews with members of the ESBC as well as group discussions with members of the seniors in the ESBC. Ultimately, upon conducting the Focus Groups, the Black in Quebec team was provided with a large amount of detailed, qualitative data derived directly from community members. This document presents the findings from the Focus Groups which are organized in two parts: challenges identified and solution based responses. Given that the Focus Group discussions were semistructured and participants offered varying levels of details, the findings reflect distinct issues or solutions identified by the participants in no particular order but were categorized thematically. Certain findings may have overlapped more than one theme.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Bill 96 and the Deaf : The Unintended Consequences of Legislation - Quebec Community Groups Network (QCGN) (2021)

Y4Y Québec Calls on the Legault Government to Consult with More Members of the English-speaking Community, and Youth in Particular, During Upcoming Bill 96 Hearings - Youth for Youth Québec (Y4Y Québec) (2021)

Quebec's English-speaking Black Community : An Analysis of the Outcomes and Information Gaps - Black Community Resource Centre (BCRC) (2021)
Black in Quebec (BIQ) is a research project being undertaken by the Black Community Resource Center (BCRC), a non-profit organization founded in 1995, which serves Montreal’s English-speaking Black Community (ESBC) by providing individuals with services and information that they need. The BIQ project seeks to answer the Research Question: What is the relative well-being of the English-speaking Black community in Quebec? The relatively unique positioning of the ESBC in the Quebec landscape, being both a visible minority and linguistic minority group, necessitates that research be conducted to further understanding of the experiences and situations facing this community, which are particular to the group or shared more widely across society. The overall vision of this project is to consolidate the collection and dissemination of data that pertains to Quebec’s English-speaking Black community and share this information across a variety of institutions, including Black community organizations, public institutions, and social research groups.

Network News - Quebec Community Groups Network (QCGN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

QCGN Statement on National Assembly Hearings on Bill 96 : QCGN Calls for Broader Participation in Bill 96 Hearings - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on National Assembly Hearings on Bill 96 : QCGN Calls for Broader Participation in Bill 96 Hearings - Quebec Community Groups Network (QCGN) (2021)

Anglophones and Francophones Share Strong Affinity for Their Respective Communities - Quebec Community Groups Network (QCGN) (2021)

Attachment to One's Language Community is Equally Important to French and English-speaking Quebecers, but Important Differences Persist in their Respective Attachments to Canada and Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (ACS) (2021)

QCGN Statement on Government of Canada’s Proposed Changes to the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Resolution 2021-01 : Free French Instruction Services for all Who Request Them - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-05 : Permanent English Voters' List for School Elections - Quebec Federation of Home and School Associations (QFHSA) (2021)

QCGN Supports Commissioner's Call for Symmetry in the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Executive Summary & Final Report - Task Force on Equity, Diversity, and Inclusion of the Lester B. Pearson School Board (2021)
The purpose of this document is to present the results of deliberations and evidence-based recommendations of the Task Force of Lester B. Pearson School Board (LBPSB) on Diversity, Equity and Inclusion.

Brief for the Consortium of Official Language Community Media, Presented to the Standing Senate Committee on Official Languages, for its Study on the Official Languages Reform Project Unveiled on February 19, 2021 by the Minster of Economic Development and Official Languages, English and French : Towards a Substantitive Equality of Official Languages in Canada - Consortium of Official Language Minority Community Media (2021)
The Consortium of Official Language Minority Community Media (the “Consortium”) is an alliance of Réseau.Presse, the Alliance des radios communautaires du Canada (“ARC du Canada”), the Quebec Community Newspapers Association (“QCNA”) and the English-Language Arts Network (“ELAN”) , the four organizations representing the interests of the entire official language minority community media sector. Since 2016, the four agencies of the consortium have spoken with a single voice on the issues affecting some 105 community newspapers and radio stations.
Keywords: Official Language Minority Community (OLMC)

Bill C-13 Weakens Federal Lifeline to English-speaking Quebec When it is Most Needed - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Preliminary Analysis of Bill 96, An Act Respecting French, the Official and Common Langauge of Québec - Quebec Community Groups Network (QCGN) (2021)
Bill 96 is a wide-ranging and complex piece of legislation. It represents a significant overhaul of Quebec’s legal system. It amends the Charter of the French Language (“CFL”), 24 other provincial statutes, one regulation, and the Constitution Act, 1867.

QCGN Calls for More Study and Debate on Quebec's Proposal : Poll Show Unilateral Amendment to Constitution of Canada Worries Most Canadians and Some Quebecers - Quebec Community Groups Network (QCGN) (2021)

Brief Presented to The House of Common Standing Senate Committee on Official Languages Submitted by the Quebec English School Boards Association - Quebec English School Boards Association (2021)
The Quebec English School Boards Association was founded in 1929. The role of the association is to represent the nine English school boards of Québec as well as the Littoral School Board, a special status school board. Our member boards cover the full geographic territory of Québec with some board territories covering more than 400,000 square kilometres, equal to the land area of Spain. Our board student enrolments range from 1,300 (Eastern Shores in the Gaspé region) to more than 25,000 for each of the 2 boards serving the Island of Montr al. Our network is comprised of about 340 schools and adult centres, some with enrolment well below 100 to as many as 2,000. Our boards serve the youth sector from Kindergarten to Secondary V (grade 11). They also deliver Adult Education and Vocational Training. Some of our boards offer pre-kindergarten programs to 4-year-old children and the Adult and Vocational sectors cater to students 16 years of age and older. All told there are approximately 100,000 students in the minority-language English public school system.

Quebecer's Views on Language Issues in the Aftermath of Bill 96 - Quebec Community Groups Network (QCGN); Association for Canadian Studies (ACS) (2021)

Proposed Bill 101 Overhaul Disgregards Fundamental Human Rights and Freedoms - Quebec Community Groups Network (QCGN) (2021)

Many Reasons to Participate in Census - Quebec Community Groups Network (QCGN) (2021)
Keywords: Official Language Minority Community (OLMC)

Anglophone and Francophone Desire to Stay or Leave Quebec : A Study of Quebec-born Undergraduates in Montreal - Bourhis, Richard Y.; Sioufi, Rana (The Charter : Bill 101 and English-Speaking Quebec/La Charte : La loi 101 et les Québécois d’expression anglaise, 2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Use of Notwithstanding Clause Would Run Roughshod Over Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2021)

What Exactly is the Notwithstanding Clause, and Why Does it Matter? - Quebec Community Groups Network (QCGN) (2021)

Did the Black Lives Matter Movement Help English-speaking Black Young Adults in Quebec Recover from the Damaging Psychological Effects of the COVID-19 Pandemic? - Koestner, Richard; Holding, Anne C. (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The historic events of the spring of 2020—the collision of the worst public health crisis in a century and the largest Black civil rights movement in half a century—offer a unique opportunity to examine how the frustrations and hopes of English-speaking Black young adults were affected. We sought to understand the potentially competing impacts that the public health and social justice crises have had on the young adults in their communities. Quebec has the second largest Black population in Canada (after Ontario), with 27% of Canada’s total Black population. Quebec’s Black population has doubled in size in the past 20 years, with 325,000 people currently living here. This population is predominantly French speaking (80%), and it is concentrated in the Montreal metropolitan area (over 90%). The Black population tends to be younger than the Canadian average, and its members are more likely to be first-generation Canadians.

Brief to the Expert Panel on Language of Work and Service in Federally Regulated Private Businesses - Jennings, Marlene; Shaar, Kevin (Quebec Community Groups Network (QCGN), 2021)
Canada has two official languages and two official language minorities. In its recent paper on official languages, English and French: Towards a Substantive Equality of Official Languages in Canada, the Government of Canada makes a legislative proposal to increase the use of French in federally regulated private enterprises. The paper outlines specific proposals to provide rights to work and rights to services in French – but not in English – in federally regulated private businesses in Quebec and in regions with a strong Francophone presence.

Preliminary Analysis of Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
Like Bill C-32, the Bill retains the same overall purposes and structure of the OLA. As with Bill C-32, the Bill sets out several new Preamble clauses, additions to the OLA’s purpose clause, and new interpretive clauses. These are all largely the same as Bill C-32, although the Bill adds a few additional clauses. In the discussion below, there is no change from C-32 except where otherwise indicated. The Bill adds the following policy priorities to the OLA: First, the protection and promotion of the French language; second, the addition of new interpretive clauses; third, the continued recognition of English and French linguistic minority communities (OLMC’s); third, the recognition of provincial language regimes including the Charter of the French Language. Finally, the Bill adds additional mention of Indigenous languages and a mention that the OLA applies in emergencies
Keywords: Official Language Minority Community (OLMC)

Quebec Community Groups Network Preliminary Analysis of Bill C-13 : An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
This document presents an overview of Bill C-13. This is not a comprehensive analysis of the Bill. Rather, it is informed and directed at priority areas of the QCGN.

Understanding an Official Language Minority Community - Quebec Community Groups Network (QCGN) (2021)
Keywords: Official Language Minority Community (OLMC)

Quebec Past and Present : 9th Colloquium on Quebec Studies / 9ème colloque sur les études québécoises - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2021)

Federally Regulated Businesses and the New Languages Landscape - Quebec Community Groups Network (QCGN) (2021)

Evaluation of the Quebec Community Health and Social Service Foundation's (QCHF) Patient Navigator Project - Anastasopoulos, Vanessa (2021)

Overcoming Language Barriers in Health and Social Services - Bilodeau, Nancy (2021)

CHSSN Survey to Access to English-language Health and Social Services - Community Health and Social Services Network (CHSSN) (Building Together, 2021)

English and French : Towards the Substantive Equality of Official Languages in Canada - Quebec Community Groups Network (QCGN) (2021)
The Government of Canada’s paper on official language reform captures important demands made by the English-speaking community of Quebec during consultative processes related to the modernization of the Official Languages Act. There is reason for optimism around proposals for an expanded role of Treasury Board and power of the Commissioner of Official Languages in the implementation of the Act. And there are opportunities for increased support to our community’s institutions and provisions for more transparency on federal transfers directed towards our vitality; proposals that are tempered by the need for provincial cooperation.

QCGN Cautiously Optimistic About Ottawa's Plan to Overhaul the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Just How Many of Us English-speaking Quebecers Are There? - Quebec Community Groups Network (QCGN) (2021)

QCGN Analysis of Quebec's Five Orientations to Modernize Canada's OfficialLanguages Act - Quebec Community Groups Network (QCGN) (2021)
Quebec’s proposal belies a fundamental misunderstanding of the history, purpose, and application of the OLA. It takes direct aim at the division of powers contained in the Constitution Act, 1867, seeking to extend Quebec’s legislative jurisdiction. The Government of Quebec is demanding exclusive authority to act in matters of language, “on its territory”. This poses an existential threat to the official language rights of all Canadians, French and English.

By the Numbers : How are Communities Counted? - Quebec Community Groups Network (QCGN) (2021)

Canada Must Not Abandon its Leadership on Official Languages - Quebec Community Groups Network (QCGN) (2021)

QCGN Asks Minister Roberge to Fund LEARN to Tutor English-speaking Students - Quebec Community Groups Network (QCGN) (2021)

The Importance of Symbolism to the English-speaking Community in Québec - Lopes-Luchak, Milla (Youth for Youth Québec (Y4Y Québec), 2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Working Together to Strengthen the Voice of English-speaking Quebec - Quebec Community Groups Network (QCGN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

2021 Community Vitality Survey : Black in Quebec - Black Community Resource Centre (BCRC) (2021)
This report offers a comprehensive overview of the 2021 Community Vitality Survey which was conducted by the Black in Quebec project team. Black in Quebec was launched in Fall 2019 and was a research project by the Black Community Resource Centre (BCRC) which researched the well-being and vitality of Quebec's English-speaking Black Community (ESBC). This is the third report to be released by the project team and complements the two previous research based publications. The first published report was Quebec's English-speaking Black Community: An Analysis of Outcomes and Information Gaps which was based on an assessment of currently available information pertaining to the English-speaking Black Community in Quebec. The second report to be released was entitled Black in Quebec presents: In Focus and it presented an overview of the Focus Groups conducted by the project team from May to December of 2020. This report focuses exclusively on the 2021 Community Vitality Survey which was conducted from April to June 2021 and provides a detailed overview of the survey. It is the last research based report to be released by the Black in Quebec project before the release of a final, comprehensive project summary report.

Black in Quebec : Summary Report 2020-2021 - Black Community Resource Centre (BCRC) (2021)
In Quebec, there is a population of around 320,000 people who identify as members of the Black community. In Quebec's Black community, just under 60,000 (around 1 in 5 people) are categorized as members of the English-speaking community (Statistics Canada, 2016). The Black in Quebec Project commenced in Fall 2019 with the drafting of the project and in February 2020, the Project Researcher (John Davids) and Research Assistant (Xiaoyan Fang) were hired by the BCRC. The purpose of the project is to fill the gaps in the knowledge about the English-speaking Black Community (ESBC) in Quebec. In Quebec and Canada, there is a lack of disaggregated race-base data that measures critical variables describing the socio-economic and psycho-social status of the English-speaking Black Community. Thus, when it came to exploring the state and vitality of the ESBC, there were and continues to be deficiencies in the publicly available data and knowledge. Being a study about a population that is both a racialized and linguistic minority in Quebec, the Black in Quebec Project attempts to fill some of the gaps in the collection of data, its analysis and storage. It presents an improved understanding regarding the unique situation and challenges facing the ESBC in Quebec.

Official Languages, Diversity, and Canada's Place in the World - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Learning English and French - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Official Bilingualism and the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2021)

Challenges Around Resources and Services in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
English-language schools in Quebec struggle with diverse challenges, from urban and rural poverty to being located in isolated and remote areas. These issues impact the services and resources available to students and schools already constrained by a declining student population (Advisory Board on English Education [ABEE], 2018).
Keywords: Official Language Minority Community (OLMC)

Issues of Bilingual Education in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The percentage of Quebec’s population with French-English bilingual skills has steadily increased over the past decades, and this is the case for all Quebecers, regardless of language background (Turcotte, 2019). Quebec Anglophone youth, however, are the most bilingual, and become bilingual at a younger age than Francophone or Allophone youth. The explanation is simple: Quebec’s English-speaking parents have been able to rely on schools to develop their children’s bilingual skills, thanks to French immersion and other enriched French-secondlanguage programs (Lamarre, 1997, 2007, 2012; Magnan et al., 2018), and in some cases by crossing over to the French sector (Laperrière & Lamarre, 2006).
Keywords: Official Language Minority Community (OLMC)

Outmigration of Quebec's English-speaking Youth - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Keywords: Official Language Minority Community (OLMC)

Representation of English-speakers in Quebec's Education Ministries and Curriculum Development - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
There is a longstanding underrepresentation of English speakers in Quebec’s public sector (Cooper, Donovan, & O’Donnell, 2019). In 2019, 506 out of 53,570 regular employees (0.9%) in Quebec’s public service were Anglophones, roughly one tenth of their proportion in the total population of the province (Secrétariat du Conseil du trésor, 2019; Statistics Canada, 2017).
Keywords: Official Language Minority Community (OLMC)

The Demography of Quebec's English-language Schools: Complexity, Changes, and Community Issues - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The definition of English-speaking Quebecers is complex, evolving, and varies according to different political stakes and jurisdictions. The narrowest definition limits the population to those with English as their sole mother tongue. The broadest definition includes non-native speakers who use English with greater or equal frequency than French (Jedwab, 2010; Donovan, 2015).
Keywords: Official Language Minority Community (OLMC)

Annual Report 2021 - Committee for Anglophone Social Action (CASA) (2021)

CHSSN Montreal Community Forum : Mental Health and COVID-19 - Community Health and Social Services Network (CHSSN) (2021)
The forum brought together representatives from the provincial government, the health sector, the community, various research initiatives, and leaders from across the Island of Montreal to discuss the effects of COVID-19 on mental health for English speakers living on the Island. The event also served as a platform forcelebrating the successes of different mental health initiatives and for co-generating solutions to some of the most urgent problems facing mental health amongst English speakers in the context of COVID-19. With the goal of deepening an understanding of the impact of COVID-19 on different demographic segments of the English-speaking population of Montreal, CHSSN invited speakers working with a wide range of populations and possessing diverse lived experiences of the pandemic. The forum was designed to foster cross-sectoral and intersectional exchanges and to create a space for learning, discovery, consciousness-raising, resource-sharing, networking, and collaborating.

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

English Language Early Childhood Services : Opinion survey among English-speaking Parents in Quebec - Community Health and Social Services Network (CHSSN) (2021)

How Services Can Better Address the Realities of English-Speaking Fathers - Community Health and Social Services Network (CHSSN) (2021)
A report based on an analysis of recent surveys and public data, identified five essential ways family services can better address the realities of English-speaking fathers.

Nord-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Chaudière-Appalaches - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Abitibi-Témiscamingue - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Outaouais - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Capitale-Nationale - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Côte-Nord - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Gaspésie - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Centre - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Est - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Ouest - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Lanaudière - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Laval - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS des Îles - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS des Laurentides - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Bas-Saint-Laurent - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

2021 Virtual Conference : Addressing Access to Health Care and Social Services for Language Minorities : Best Practices and Latest Evidence - Dialogue McGill (2021)

Postsecondary Education in the Minority Language : An Overview and Analysis of the Issues - Forest, Mariève; Deschênes-Thériault, Guillaume (2021)
This study provides an overview of postsecondary education in the minority language, as well as the issues related to postsecondary education in French in a minority context. To do so, this report sketches a quantitative portrait of postsecondary education in English in Quebec and in French outside Quebec by drawing on various Statistics Canada sources – Population Census (2016), National Graduates Survey (NGS) (2018), Post-Secondary Student Information System (PSIS) (2018-2019) – and administrative databases. Based on the literature and interviews with more than 25 people involved in the administration of postsecondary education, this report provides an analysis of the dynamics and characteristics of French-language postsecondary education outside Quebec.

Postsecondary Education in the Minority Language : An Overview and Analysis of the Issues - Mariève, Forest; Deschênes-Thériault, Guillaume (Sociopol, 2021)
The advocacy efforts of Francophone minority communities (FMCs) that followed the adoption of the Official Languages Act (1969) and the Canadian Charter of Rights and Freedoms (1982) led to the development and implementation of the provincial and territorial minority-language elementary and secondary school systems. In Quebec, the implementation of the Englishlanguage elementary and secondary school system did not meet with the same level of resistance as that faced by the French-language school systems in FMCs.

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

Understanding the Experience of English-speaking Seniors in Quebec : Accessing and Interacting with Health and Social Services and the Effect on Health Outcomes - Recreo Therapy (Community Health and Social Services Network (CHSSN), 2021)

2nd Annual General Meeting 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report : 2020-2021 - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Portrait of Men and Fathers in Quebec's English-Speaking Community & Their Relationship to Services - A Sociological View - Roy, Jacques (Community Health and Social Services Network (CHSSN), 2021)
What is the profile of English-speaking men in Quebec? Are they different from other Quebec men, mainly Francophones? Has the pandemic affected them more? Do they experience additional barriers to services imply because of their language? Finally, what policies and interventions could improve their condition and access to health and social services? These are the questions at the heart of this study. In order to shed light on these issues, the research uses an examination of recent survey results and public data to map out the English-speaking community in terms of the men and fathers who comprise it. Before doing so, a culturalist analytical framework is presented to better understand and interpret the results that emerge from the various sources of information used in the study. Finally, avenues for action in terms of public policy and intervention in practice settings are proposed to improve the situation of English-speaking men and fathers and to bring health and social services closer to their needs and reality. The results of surveys and public data reports form the basis for reflection on the actions to be taken.
Keywords: Official Language Minority Community (OLMC)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

The Holland Centre Experience : A Community Development Model for Minorities - Walling, Richard (Holland Resources Development Corporation, 2021)
The Holland Centre is a partnership of four public organisations and one private non-profit community organisation that has been successful in creating culturally-appropriate health and social services for a minority community in the province of Quebec, Canada. In June 1999 the J.W. McConnell Foundation awarded a grant to the Holland Centre that allowed it the time and resources necessary to analyse the elements of the centre’s success and develop the tools necessary to assist other linguistic minority communities to develop essential services.

Annual Report 2020-2021 - Youth for Youth Québec (Y4Y Québec) (2021)

Building Bridges : Final Report on the 2019 Consultations : 2019 Consultation with Organizations Serving English-speaking Communities on the Priorities and Orientations of the Secrétariat aux relations avec les Québécois d'expression anglaise - Ravensbergen, Frances (Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA), 2020)
In the fall of 2019, the Secrétariat aux relations avec les Québécois d’expression anglaise (the “Secrétariat”) consulted with its community and institutional stakeholders in a series of 11 sessions. Overall, more than three hundred community leaders representing more than 140 organizations and institutions participated in the consultation, which gave them an opportunity to provide input on priorities and orientations for the Secrétariat.

VEQ’s Fall Winter 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

In celebration of Early Childhood Week, the Community Health and Social Services Network is pleased to present : Supporting the Well-being of Young Children in English-speaking Communities! - Community Health and Social Services Network (CHSSN) (2020)

Window Onto Local Farming : Sols en santé / Living Soil, Healthy Soil - Centre for Access to Services in English (CASE) (2020)

APPELE-Québec Slams Quebec Government for Flip Flop on School Board Elections - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

[Letter to House Leaders from Geoffrey Chambers, QCGN President] - Chambers, Geoffrey (2020)

Community Vitality Report on English-speaking International Students - Andrade, Gustavo; Morais, Maria (Y4Y Québec, 2020)
Since 2016, the first year of the QS Best Student Cities ranking, produced by QS Quacquarelli Symonds, Montreal is ranked in the top 10 best cities for students in the world. It is regularly ranked as the most student-friendly city in North America and was rated #1 in 2017. The rank’s methodology includes indicators such as university rankings, affordability, and, since 2017, students’ opinions (QS Quacquarelli Symonds, 2019). As a result, Montreal attracts tens of thousands of international students every year. Many of those students come to Quebec with English as their second language, with little to no knowledge of French, to study at both major English-language universities, Concordia and McGill, or in one of the numerous English-language private colleges. Besides all the challenges related to post-secondary studies and being an English-speaker in Quebec, English-speaking international students who want to settle in Quebec also need to face the challenge of living abroad and learning the language of the majority.

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Working Together to Strengthen the Voice of English-speaking Quebec : Report on Interviews with Key Community Leaders - Quebec Community Groups Network (QCGN) (2020)
A quarter of a century ago, the Quebec Community Groups Network was founded with a mandate to build the understanding and cooperation needed to develop strong, reasoned policy to ensure sustainable growth for English-speaking Quebec. During a strategic planning exercise in 2013, the membership approved an updated mission: The QCGN is a centre of evidence-based expertise and collective action on the strategic issues affecting the development and vitality of English-speaking Quebec. The mission and actions of the QCCN support our Network’s vision that English-speaking Quebec is a diverse, confident, recognized, and respected national linguistic minority that actively participates in and contributes to the social, economic, cultural, and political life of Quebec and Canadian society.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Substantive Overhaul for Official Languages Act is Overdue - Quebec Community Groups Network (QCGN) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Huge Victory for Minority Language Rights in Quebec's Superior Court - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

VEQ’s Summer 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Huge Victory for Minority School Boards in Supreme Court B.C. School Board Case - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people aged 15-35 filled out the survey and nine focus groups were held in a total of six communities with a total of 82 youth.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

QCGN Welcomes Wider Distribution of COVID-19 Self-care Guide to English Speaking Quebecers - Quebec Community Groups Network (QCGN) (2020)

Quebec Past and Present 2020 : Colloquium on Quebec Studies - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2020)

A Posthumous Honour for a Conspicuous Life : Dr. Gaspard in Quebec - Williams, Dorothy (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
This story is an attempt to understand an unknown individual whose life was significant but has now been forgotten. He was American-born, yet his mother tongue was French. He served Canada in French units but embraced the English-speaking Black community once in Montreal. His life speaks of a complexity of language not often explored in narratives of Quebec’s English-speaking community, particularly in those histories about Blacks in the province. I trust this will be the beginning.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

QCGN Welcomes Positive Measures for English-speaking Seniors - Quebec Community Groups Network (QCGN) (2020)

QCGN Statement on The Expert Panel on Language of Work and Service in Federally Regulated Private Businesses - Quebec Community Groups Network (QCGN) (2020)

Social Portrait of the Greenfield Park Borough (Ville de Longueuil) - Corporation de développement communautaire de l’agglomération de Longueuil (2020)

Supporting English-speaking Children and Families on the North Shore of Quebec - North Shore Community Association (NSCA) (Community Health and Social Services Network (CHSSN), 2020)

Report on the Consultation by the Secretariat for Relations with English-speaking Quebec - Quebec Community Groups Network (QCGN) (2020)
During a July 2019 visit with the English-speaking community of Grosse-Île, in the Magdalen Islands, MNA Christopher Skeete, the Parliamentary Assistant to Premier François Legault for Relations with English-speaking Quebecers, announced a province-wide consultation. Scheduled for Fall 2019, the stated goal was to develop an action plan to address the priorities of Quebec’s English-speaking community in collaboration with the Secretariat for Relations with English-speaking Quebecers. Meetings with community stakeholders were held in regions throughout Quebec. These culminated with a sectoral meeting in Quebec City on November 15, 2019. QCGN representatives participated as observers at all of the meetings. We made a presentation at the sectoral meeting.
Keywords: Official Language Minority Community (OLMC)

VEQ’s Spring 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

English-speaking Community Challenges the Constitutionality of Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

Premier Legault Attempts to Muzzle English-speaking Community - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

APPELE-Québec Deplores Government Haste in Involving Closure on Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

Annual Report 2020-2021 - Community Health and Social Services Network (CHSSN) (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Making a Difference in the Laurentians - LESAN (2020)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 - Pocock, Joanne (Community Health and Social Services Network, 2020)
The Baseline Data Report 2019-2020 (BDR) is the eighteenth volume of a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the situation of Québec’s English-speaking population in the area of health. The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Estrie-CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Ouest-de-l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English language Health and Social Services in Québec : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Centre Ouest de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Centre Sud de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Nord de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

Annual Report : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Closing the 12k Gap : Improving Employment for Quebec's English Community - Conference Report - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Youth Employment Services (YES) is pleased to have secured funding from the Secretariat for relations with English-peaking Quebecers (SRQEA) to build a stronger network of English service organizationsworking in employability. The Provincial Employment Roundtable (PERT) project aims to address three important employment issues facing English speakers in Quebec.

Annual Report 2020 - Youth for Youth Québec (Y4Y Québec) (2020)